2001
DOI: 10.1177/136140960100600408
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the pre-registration preparation of nurses to work in secure environments

Abstract: As part of the UKCC Nursing in Secure Environments project, all pre-registration programme providers for mental health and learning disability were contacted and invited to complete a questionnaire concerning their involvement with, and preparation of, nurses for working in these settings. Details are provided of the analysis of these questionnaires, along with parallel data captured from the project's focus groups and from focused interviews which provided a commentary of the practitioners' views concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the need for in‐service programmes for forensic nursing in secure psychiatric services had become a growing concern internationally. Storey & Dale (2001) conducted an examination of the pre‐registration preparation of nurses to work in secure environments. The author's findings indicated that practitioners were not adequately prepared for work in these specialized environments.…”
Section: Studies Recommending a Need For Forensic Nursing Educationmentioning
confidence: 99%
“…In addition, the need for in‐service programmes for forensic nursing in secure psychiatric services had become a growing concern internationally. Storey & Dale (2001) conducted an examination of the pre‐registration preparation of nurses to work in secure environments. The author's findings indicated that practitioners were not adequately prepared for work in these specialized environments.…”
Section: Studies Recommending a Need For Forensic Nursing Educationmentioning
confidence: 99%
“…Staff noted the following barriers to the provision of appropriate support: lack of time for team debrie ng; the ad hoc nature of supervision; lack of formal supervision structures; and lack of specialist rather than general support. Indeed, the paucity of supervision and support for staff working with women in secure environments has also attracted attention from the UKCC in their recently published 'scoping' study on 'Nursing in Secure Environments' (Storey and Dale, 1999). 1…”
Section: Supervision and Supportmentioning
confidence: 99%